(untitled) (Proceedings of the International Conference on Social Sciences, 2018)
Human development is a process of growth and change that begins at conception and continues throughout the life span. It involves changes in biological, socioemotional, and cognitive domains that are inextricably intertwined. These changes are crucial for children to function successfully in their living environment. An enormous amount of research has indicated that both prenatal and postnatal experiences, microsocial as well as macrosocial interactions, and socio-cultural factors significantly influence the process of development. Also, it has been observed that new ways of understanding and responding to the world emerge at particular times in life; therefore, certain ages are crucial for the growth and changes of major domains of human development. According to developmental psychologists, behavior is not a context-free phenomenon; instead, it is a product of an interaction between the individual and his socio-cultural context. Therefore, many theorists have highlighted the importance of understanding the process of development and human behavior within the sociocultural context in which people live. The purpose of this paper is to discuss important principles and factors including prenatal and postnatal experiences, developmental changes in particular stages in life, and socio-cultural factors that significantly contribute to the process of development.